Biodiesel production from fish (Cyprinus carpio) waste and evaluation of engine performance - Mohammed Saifuddin,; Amru N. Boyce, (Penerbit Universiti Kebangsaan Malaysia, 2017)
As fossil energy resources are depleting quick and energy security is playing a vital role in the world economy. Quest for alternative energy sources have turned researches investigation in waste foods for next generation fuel. Biodiesel is usually considered to be environmentally friendly as it reduces greenhouse gas emission. Fish wastes rich in fatty acids and can be used as the raw material to produce biodiesel through transesterification reaction. The results showed that the seven peaks are fatty acid methyl esters, indicating all the triglycerides were successfully methylated to methyl esters. Fish based biodiesel provided a significant reduction in carbon monoxide (CO) and hydrocarbon (HC) emissions under engine loads of 15 (Nm) and required no engine modification. The viscosity of the produced biodiesel was within the range of international standards (ASTM). The biodiesel was found to contain a low base number and exhibited a lower specific fuel consumption compared to the conventional diesel. It can be concluded that biodiesel derived from waste fish oil can be considered as a potential source of commercial biodiesel.